Diabetes Mellitus in Geriatric Dog in Paws Vet Padang Clinic: A Case Report - Rianda, Teguh; Rahayu, Hesti; Sugito, Sugito; Erwin, Erwin; Rosa, T Shaddiq; Fakhrurrazi, Fakhrurrazi (Jurnal Medika Veterinaria, 2024)
Diabetes mellitus is a common disorder in middle-aged and geriatri dogs. Diabetes mellitus occurs when the pancreas does not produce enough insulin or when the bodys cells do not respond well to insulin. Geriatri dogs, neutered males, specific breeds, glucocorticoid treatment and concurrent hyperadrenocorticism or pancreatitis are all associated with DM diagnosis in dogs. A twelve year-old male mix Corgi dog weighing 4.5 kg showed clinical signs of polyuria, polydipsia, polyphagia, and a very significant reduction in body weight. Blood biochemical analysis showed an increase in blood glucose levels up to 847 mg/dL. This dog was diagnosed with diabetes mellitus. The patient was given therapy in the form of feed replacement using special diabetic feed (Royal Canin Diabetic food ) and insulin glargine injection at a dose of 0.25 IU/kg twice a day before meals. After two weeks of therapy, the patient showed good progress as indicated by lowering blood glucose levels to 322 mg/dL and decreasing clinical symptoms in the form of polyuria, polydipsia, and polyphagia